A cross-sectional study of subclinical and clinical thyroid disorders in women with microscopic colitis compared to controls. (December 2013) - J. Gustafsson, Rita; Roth, Bodil; Lantz, Mikael; Hallengren, Bengt; Manjer, Jonas; Ohlsson, Bodil
Abstract Background and aims. Microscopic colitis (MC), predominantly affecting women, is associated with thyroid disorders, although purely defined of which type, or compared with controls. Its association with subclinical thyroid disorders, and related increased risk of cardiovascular diseases, has never been examined. The aim was to examine the prevalence of autoantibodies and subclinical and clinical thyroid dysfunction in female patients with MC compared with controls. Methods. Women younger than 73 years old with biopsy-verified MC from the Department of Gastroenterology in Skåne, during 2002–2010, were invited. Out of 240 identified, 133 were finally included. A questionnaire about medical history was completed and blood samples were collected. Serum was analyzed for free thyroxin and triiodothyronine, thyroid-stimulating hormone and anti-thyroid peroxidase (anti-TPO) antibodies. A population-based group of 737 women served as controls. Result. The prevalence of thyroid disorders in patients was higher compared to controls [odds ratio (OR) = 2.98, 95% confidence interval (CI) = 1.78–4.99], but the prevalence of subclinical disorders was not different (OR = 1.18, 95% CI = 0.48–2.85). Anti-TPO antibodies were present in 10.6% of MC patients and 18.6% of controls. Twenty-five MC patients had hypothyroidism: 15 with Hashimoto´s hypothyroidism, 6 with completed treatment of thyrotoxicosis and 4 with completed surgery after nontoxic goiter. Conclusion. Thyroid disorders, autoimmune hypothyroidism being most frequent, are more prevalent in patients with MC than in controls, whereas the prevalence of subclinical thyroid disorders in MC patients does not differ significantly from controls.